The contested moralities of markets - Schiller-Merkens, Simone; Balsiger, Philip (Bingley, U.K. : Emerald Publishing Limited, 2019)
Moral struggles in and around markets abound in contemporary societies where markets have become the dominant form of economic coordination. The present volume advances our current understanding of markets by highlighting the sources, processes and outcomes of moral struggles in and around markets. It traces the creation, reproduction and change of underlying moral orders and reveals the role of status and power differentials, alliances and political strategies as well as the general cultural, social and political contexts in which the struggles unfold. The contributions to this volume reflect the 'moral turn' that can currently be observed in organization studies and economic sociology, and connect to recent developments in the sociology of morality.
Includes index.
Keywords: Financial institutions -- Moral and ethical aspects; Capital market -- Moral and ethical aspects; Financial institutions -- Social aspects; Social Science -- Sociology -- General; Sociology: work & labour